1994
DOI: 10.1007/bf02412809
|View full text |Cite
|
Sign up to set email alerts
|

The water rise in front of a model planing hull

Abstract: It is known that the water "splashes-up" or rises above the undisturbed surface immediately in front of a planing surface. This rise is greatest in front of a flat planing plate and a number of attempts have been made to reduce the experimental measurements of this phenomenon to some kind of order. Since it was first independently proposed by both Schnitzer and Smiley in 1952, all attempts to correlate the flat plate splash-up have started with the assumption that splash is only a function of the immersed leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…There was some evidence for this type of jet when the stream velocities were higher than in the experiments reported in § 2. In those reported, however, in common with other experiments on planing hulls (Payne 1994), the recirculating jet collapsed and evolved into a foaming wedge such as is seen in figure 2. Thus, a normal force of the form (3.4) seems inappropriate, and we present a more obviously relevant, if crude, alternative in § 4.…”
Section: Equation Of Motion Of the Paddlesupporting
confidence: 67%
See 1 more Smart Citation
“…There was some evidence for this type of jet when the stream velocities were higher than in the experiments reported in § 2. In those reported, however, in common with other experiments on planing hulls (Payne 1994), the recirculating jet collapsed and evolved into a foaming wedge such as is seen in figure 2. Thus, a normal force of the form (3.4) seems inappropriate, and we present a more obviously relevant, if crude, alternative in § 4.…”
Section: Equation Of Motion Of the Paddlesupporting
confidence: 67%
“…Such a jet is observed in our experiments when the paddle enters the fluid during skipping. In the steady planing state, however, we see that any such jet collapses rapidly to create a turbulent wedge of fluid much like that preceding the bow of a ship (Payne 1994; see figure 2).…”
Section: Introductionmentioning
confidence: 93%
“…By neglecting the pile-up of water at the keel line, L k is obtained from the undisturbed water-level intersection with keel line. Such an assumption is, according to Savitsky’s statement for dead-rise planing surfaces, 3 “up to trim angle of approximately 15 deg there appears to be no noticeable pile-up of water at keel line.” In this regard, Payne 53 by analyzing the previous data gives a simple relation to calculate water rise in front of prismatic planing surfaces. In his relation, the increase in wetted length due to such water splash-up is proportional to sin τ and for a prismatic hull with dead-rise angle of 20° (according to suggested exponentially decaying dependency on dead-rise angle) is approximately 2.5 times less than that for flat plate (zero dead-rise angle).…”
Section: Resultsmentioning
confidence: 99%
“…In these references, it is mentioned that accurate transient rise measurement is very difficult. In this context, Payne 13 considered the water ''splash-up'' or rise above the undisturbed surface immediately in front of a planing surface. He surveyed the attempts that had been made to reduce the experimental measurements of the flat plate planing.…”
Section: Introductionmentioning
confidence: 99%
“…15 All of them had concluded that, when the wetted length to beam ratio exceeded (roughly) unity, the increase in wetted length due to splash-up was approximately 30%-40% of the beam. 13 Payne 16 summarized some of these attempts in his book.…”
Section: Introductionmentioning
confidence: 99%